Overcapacity in Indonesia’s Prisons: The Role of Criminal Law Reform in Sustainable Solutions - Prabawani, Riski Dysas; Pujiyono, Pujiyono; Roikardi, Dodi (Journal of Law and Legal Reform, 2025)
Overcrowding is an unresolved problem occurred in Indonesia. So far, most criminal acts are threatened with a criminal sentence in the form of imprisonment. The reform of this Indonesian criminal law has been realized with the enactment of Law Number 1 of 2023. This research aims to examine the contents of Law Number 1 of 2023 concerning the Criminal Code as an update to the Criminal Code/Wetboek van Strafrecht (WvS), which has been in force in Indonesia. This is the doctrinal research with a conceptual and comparative approaches. The findings show that the revised Criminal Code introduces a novel approach to criminal law by explicitly outlining the objectives and guidelines for punishment, thereby directly influencing law enforcement practices. Furthermore, this new Criminal Code also provides alternative sanctions other than imprisonment.